Nurses’ attitude toward the care of dying cases in the cardiac center in Erbil city - Abdulla, Salih A.; Sheren, Nazar Ali; Naqshbandi, Vian A.; Al-Tawil, Namir G. (Zanco Journal of Medical Sciences (ZJMS), 2014)
<p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Background and objective: Nurses play a key role in providing care at the end of life; death is inevitable that affect every human being. Nurses are present at both the beginning and the end of life and play a key role in caring for dying patients. The aim of this study was to assess the attitudes of critical care nurses toward care of the dying as well as assessing the relationship between demographical components and attitudes toward care of the dying. <p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Methods: A cross-sectional study was carried out in the cardiac center of Erbil city, Iraqi Kurdistan region, during the period from 2nd February to 4thof March, 2013. A convenience method of sampling was used to collect 40 nurses working in that center. The mean age(±SD) of nurses were 27.87 (±2.92, range=35-24). Each nurse was asked to complete the Frommelt Attitudes toward Care of the Dying Scale (FATCOD) and demographics questionnaire designed and copyrighted by Katherine Frommlet in 1988. <p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Results: The study indicated that there was positive attitude among study samples. Results showed that no significant relationship between attitudes score with gender, nurse education, and duration of service, while there was significant association between high attitudes score with older ages (P = 0.003). <p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Conclusion: The nurse’s attitudes toward dealing with dying cases were positive in the majority of related items, and there were no associations between gender, duration of experience, and level of education and their attitude, while it was found a significant association between ages and attitudes towards care of the dying.